Plasma metals and cardiovascular disease in patients with type 2 diabetes. (August 2019) - Long, Tengfei; Wang, Ruixin; Wang, Jing; Wang, Fei; Xu, Yali; Wei, Yue; Zhou, Lue; Zhang, Xiaomin; Yuan, Jing; Yao, Ping; Wei, Sheng; Guo, Huan; et al.
Abstract: Background: Metals exposure from natural environment and pollution have been linked to cardiovascular disease (CVD). However, whether associations existing between plasma multiple metals and incident cardiovascular disease in patients with type 2 diabetes (T2D) is unknown. Objectives: We conducted a prospective cohort study to investigate whether plasma levels of metals are associated with incident CVD risk in patients with T2D. Methods: In a prospective study of 3897 type 2 diabetes embedded in the Dongfeng–Tongji cohort, fasting blood samples were collected in 2008 at baseline and in 2013 in the first follow-up period. Plasma concentrations of 23 metals were measured by inductively coupled plasma mass spectrometry (ICP-MS). The associations between plasma metal concentrations and CVD risk in patients with T2D were investigated with Cox proportional hazards models. Results: During an average of 6.2 years follow-up, 1114 participants developed CVD. In the single-metal models adjusting for established cardiovascular risk factors, plasma zinc and selenium levels were negatively and strontium was positively associated with incident CVD risk in patients with T2D. Similar results were obtained in the multiple-metal model, the HRs (95% CIs) for zinc, selenium, and strontium comparing extreme quartiles were 0.78 (95% CI: 0.65–0.93; P trend = 0.011), 0.76 (95% CI: 0.64–0.91; P trend = 0.001), and 1.51 (95% CI: 1.26–1.81; P trend <0.001), respectively. In the joint association analyses of two metals, individuals with high plasma levels of zinc and selenium had significantly lower risk of incident CVD in patients with T2D than those with low levels (HR = 0.77, 95% CI: 0.65–0.91). Conclusions: The present study suggested that plasma levels of zinc and selenium had an inverse association with incident CVD risk in patients with T2D, while strontium had a positive correlation. Plasma zinc and selenium combinedly decreased incident CVD risk in patients with T2D. Further research is still needed to verify these findings in other populations. Highlights: We investigate the association between plasma levels of metals and incident CVD risk in patients with T2D. Plasma zinc and selenium were negatively and strontium was positively associated with incident CVD risk among T2D cases. Plasma zinc and selenium combinedly greatly decreased incident CVD risk in patients with T2D.